Return to South Town - Graham, Lorenz B. (New York : Crowell, 1976)
In spite of the difficulties it might bring, David Williams, now a full-fledged doctor, returns to establish his practice in the Virginia town where he had lived as a boy.
Keywords: African Americans -- Juvenile fiction; African Americans -- Fiction; Race relations -- Fiction